Lektologijos statusas ir jos tolesnės raidos perspektyvos - Samėnas, Alvydas (Knygotyra, 1983)
The article analyses methodological problems of recent reading investigations. Some scholars consider lectology to be a complex science. The author holds the view it is the sum total of different subjects and trends (that claim independence). The object of lectology (as a complex science) is reading activity. It is investigated as wholeness of a system “reading material-reading-reader” in order to ascertain the regularities of its functioning and development. In this case the structure of lectology would be as follows: 1. General theory of reading. 2. Sociology of reading. 3. Psychology of reading. 4. Pedagogics of reading. 5. History of reading investigation. The guestion of integration of these subdivisions has not been solved yet. Further perspective of lectology depends directly on the answer to the guestion of the possibility of existence of complex sciences. Opinions differ here. The status analysis of the science of science, the science of book shows us that lectology could develop as a) complex science. b) noncornplex science based on the general theory of reading, c) complex problem.